Effects of initial weight on growth criteria of grass carp, Ctenopharyngodon idella cultivated in earthen ponds - Taher, Majid M.; Muhammed, Sadig J.; Al-Dubakel, Adel .Y.; Mojer, Ahmed M. (Mesopotamian Journal of Marine Sciences, 2021)
The current experiment was conducted in the Agricultural Research Station-Aquaculture Unit, College of Agriculture, University of Basrah from 27th June to 10th Nov 2020 in Al-Hartha District about 16 km northern-east of Basrah Governorate (30o65`64.6"N, 47o 74`79.5"E). Six earthen ponds (600 m3) were used to investigate the effect of three different initial weights of grass carp, Ctenopharyngodon idella [220.1-276.8 g (T1); 146.5-169.3 g (T2); 81.5-82.7 g (T3)]. Fishes were fed 3% daily using commercial pellets manufactured by Agricultural Consultant Office. The results of the current study indicated that T1 had better growth criteria (WI= 296.8 g, DGR= 2.53 g/day, SGR= 0.59%/day and FCR 5.23) compared with the other two treatments. There was a negative allometric pattern of growth (b less than 3) in the three treatments before and after the experiment. Statistical analysis of the results proved that there were significant differences (P≤0.05) in the modified condition factor (Kb) between the three treatments at the end of the experiment, while there were no significant differences (P>0.05) in the relative condition factor (Kn) and Fulton’s condition factor (K). It was concluded from the current experiment that the initial average weight of the grass carp must not be less than 250 g to achieved good results for fish culturist.